Genderwise Investigation of Empahty Skills in Child Athletes - Yasin Arslan; Gülfem Sezen Balçıkanlı (Türk Spor ve Egzersiz Dergisi)
ABSTRACTThis study intends to investigate the empathy skills in child athletes with regard to gender. The study group comprises 226 children selected randomly from various clubs in Ankara. 56.7% of the total number is female and 40.3% is male. When the sports age of the group with a mean age of 12.16 is examined, it can be seen that 40.7% have been doing sports for 1-2 years, 42.0% have been doing sports for 3-4 years and 17.3% have been doing sports for 5-6 years. The study group is distributed into branches, with 29.2% pertaining to volleyball, 42% to handball, and 28.8% to basketball. In the study, 'Empathy Scale for Children' developed by Bryant (3) and adapted to Turkish by Yüksel (23) was used as data collection tool. The frequency, percentage distributions and the mean values of the sub-dimensions of the scales were calculated. Independent Samples T-test was used to determine the empathy levels of the child athletes. When the findings were examined, it was seen that the empathy levels of the child athletes differed according to gender and this difference was statistically significant in favor of girls (p=.00). As a result, the activities aiming to improve the sportspeople’s taking roles and perspectives along with empathetic thinking skills should be included in the process of creating empathetic people thus empathetic sensitivity should be increased.